Akselerasi Literasi Digital dan Kapabilitas Strategis Mahasiswa dalam Menyongsong Visi Indonesia Emas 2045 - Afifah Khaerani A (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
A national seminar titled "The Role of the Young Generation in Welcoming Indonesia Gold 2045" was organized as a strategic effort to educate and provide insights to the youth regarding their tangible contributions across various development sectors. This community service initiative was conducted at Salakanagara University, involving expert speakers in the field of informatics to discuss the relevance of technology in achieving the national vision. The methodology included socialization through material presentation, interactive discussion forums, and hybrid Q&A sessions (offline and online). Evaluation results indicated high participant enthusiasm with a total attendance of 105 people. Despite minor technical issues with the digital platform and space constraints, the activity successfully raised participant awareness of future challenges. Key recommendations include improving time management and infrastructure facilities for future events to optimize material delivery and participant interaction.